COMPARATIVE EVALUATION OF REPRODUCTIVE PERFORMANCE OF GRADED AND CROSSBRED CATTLE OF CHHATTISGARH IN FIELD CONDITION - KHUNTE, N; MUKHERJI, K; JAIN, V; PATEL, B (The Indian Journal of Animal Reproduction, 2017)
The present study was undertaken to assess the reproductive performance of crossbred (Holstein Friesian/ Jersey crossbred) and graded (Gir, Sahiwal and Red Sindhi grade) cattle (n=200) in Chhattisgarh. The age at first calving and dry period for crossbred cattle was lower (p
Keywords: Cattle; Crossbred; Graded; Nutrition; Reproductive performance